Ionophore coccidiostats – disposition kinetics in laying hens and residues transfer to eggs - Abubakar Bello; Jérôme Henri; Alexis Viel; Jonathan Paul Mochel; Błażej Poźniak (Poultry Science, 2023)
ABSTRACT: Poultry production is linked with the use of veterinary medicinal products to manage diseases. Ionophore coccidiostats have been permitted for use as feed additives within the European Union (EU) for the prevention of coccidiosis in various species of poultry with except of laying hens. The presence of chemical residues in eggs is a matter of major concern for consumers’ health. Despite such prohibition of use in laying hens, they were identified as the most common non-target poultry species being frequently exposed to these class of coccidiostats. Many factors can influence the presence of residues in eggs. Carryover of these class of coccidiostat feed additives in the feed of laying hens has been identified as the main reason of their occurrence in commercial poultry eggs. The physicochemical properties of individual compounds, the physiology of the laying hen, and the biology of egg formation are believed to govern the residue transfer rate and its distribution between the egg white and yolk compartments. This paper reviews the causes of occurrence of residues of ionophore coccidiostats in eggs within the EU with special emphasis on their disposition kinetics in laying hens, and residue transfer into eggs. Additional effort was made to highlight future modeling perspectives on the potential application of pharmacokinetic modeling in predicting drug residue transfer and its concentration in eggs.